AFFECTIVE AND COGNITIVE ISSUES OF ENHANCING GRAMMATICAL COMPETENCE - VOVK, Olena (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2021)
This study presents the framework of mastering English grammar within a University curriculum. Fostering learners’ grammatical competence is identified as a current target of grammar acquisition. The idea is emphasized that to achieve a target set the teacher has to take into account multiple factors, which might facilitate grammatical awareness of students. Specifically, enhancing grammatical competence can be efficacious provided that the teacher considers cognitive profiles of students and reckons in such affective determinants as individual mental and psychological differences of learners, their brain capacity, learning strategies, epistemic and cognitive styles, sensory channels of perceiving input, and ways of processing information.